3D‐printed and foamed triply periodic minimal surface lattice structures for energy absorption applications. Issue 4 (31st January 2023) - Weber, Dylan; Srinivas Sundarram, Sriharsha
Abstract: Structures currently used for energy absorption include foams, composites, and honeycombs. Recent studies have indicated the potential of triply periodic minimal surfaces (TPMS) for energy absorption applications as well as weight reduction. This study presents three TPMS lattice structures, namely the Gyroid, Fischer‐Koch S, and PMY, which are fabricated in uniform and graded densities. These structures, created in the MSLattice software are 3D printed using polylactic acid. Subsequently, the 3D‐printed structures undergo a gas foaming process to investigate benefits of higher porosity on energy absorption. The structures are then characterized for porosity, compressive properties, energy absorption, and thermal properties. The results show that the uniform and graded density structures have similar energy absorption values as long as the structures have a similar average density with the PMY structure exhibiting the highest energy absorption value, both in unfoamed and foamed conditions, respectively. The foaming process increased the porosity by 50% but did not improve the energy absorption characteristics of any of the structures with the foamed PMY structures exhibiting the least deviation compared to the unfoamed samples. These foamed TPMS structures are suitable for applications in the automotive and aerospace industry that demand lightweight structures for energy absorption. Abstract : This study presents three TPMS lattice structures, namely the Gyroid, Fischer‐Koch S, and PMY, which are 3D printed using polylactic acid. Subsequently, the 3D printed structures undergo a gas foaming process to investigate benefits of higher porosity on energy absorption